Effect of Pitch Angle on Structural and Aerodynamic Characteristics of Vertical-Axis Wind Turbines (VAWTs) Using Leading-Edge Protuberance Blades - Karthikvel Elangovan; S. Nadaraja Pillai (Energies)
An experimental investigation was carried out to understand the effects of LEP (leading-edge protuberance) blades on the structural characteristics of VAWTs. A series of experiments were performed on VAWTs with straight and LEP blades for a wide range of wind velocity (6 m/s to 20 m/s) and pitch angles (−20° to 20°), and the structural excitations on the VAWT structure were measured using a triaxial accelerometer in each case. The raw acceleration data were extensively processed in the time and frequency domains to identify the variation in structural excitation caused by the unsteady wind and aerodynamic loads on the VAWT structure. Understanding the aerodynamic changes and their impact on structural characteristics is essential. The current study examines how LEP influences the structural excitation of VAWTs. However, a great deal of aerodynamic variation was observed for the LEP blades, so the straight blades of the VAWT were replaced with various modified LEP blades, for which a similar set of experiments was carried out. The study presents a better performance (self-starting, stall-mitigating) for VAWTs with LEP 3 and 2 blades, with a significant reduction in the excitation of loads due to wind load and the changes in aerodynamics observed in the along- and across-wind directions.